2016
DOI: 10.1108/f-07-2014-0060
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability in facilities management: an overview of current research

Abstract: Purpose Climate adaptation, energy efficiency, sustainable development and green growth are societal challenges for which the Facilities Management (FM) profession can develop solutions and make positive contributions on the organisational level and with societal-level effects. To base the emerging sub-discipline of sustainable facilities management (SFM) on research, an overview of current studies is needed. The purpose of this literature review is to provide exactly this overview. Design/methodology/approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
84
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(87 citation statements)
references
References 59 publications
0
84
0
3
Order By: Relevance
“…A survey by Elmualim et al (2010) identified three areas where a majority of respondents were active: energy management, waste management & recycling and health & safety. Published research on sustainable facilities management can be assigned to eight categories: building performance; sustainability tools and standards; user perception, satisfaction and productivity; sustainability management; construction and sustainable building materials; building design and sustainability; urban development; and benefit of green buildings (Nielsen et al, 2016). The growing concern with sustainable facilities management implies that the ISO 41001:2017 Vocabulary definition of FM appears as limited and outdated because it concentrates exclusively on the organizational impact FM services have and also fails to acknowledge the environmental impact.…”
Section: Sustainabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…A survey by Elmualim et al (2010) identified three areas where a majority of respondents were active: energy management, waste management & recycling and health & safety. Published research on sustainable facilities management can be assigned to eight categories: building performance; sustainability tools and standards; user perception, satisfaction and productivity; sustainability management; construction and sustainable building materials; building design and sustainability; urban development; and benefit of green buildings (Nielsen et al, 2016). The growing concern with sustainable facilities management implies that the ISO 41001:2017 Vocabulary definition of FM appears as limited and outdated because it concentrates exclusively on the organizational impact FM services have and also fails to acknowledge the environmental impact.…”
Section: Sustainabilitymentioning
confidence: 99%
“…In Table III we link articles dealing with sustainability in this special issue to the eight categories of sustainable facilities management defined by Nielsen et al (2016). The article by Collins et al connects to the three categories of building performance, building design and sustainability and benefit of green buildings in exploring how to close the gap between sustainable buildings and sustainable facilities management.…”
Section: Articles In This Issuementioning
confidence: 99%
See 1 more Smart Citation
“…The application of performance measurement has been embraced in FM through in-depth analysis (Enoma & Allen, 2007). In addition, most recently, sustainable facility management has become one of the primary research themes in the field of FM (Nielsen, Sarasoja, & Galamba, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…If a WM company looks to provide procurement and cleaner production services some potentials identified in the IE literature include designing products and process to use less, shifting to biologically inspired production models, and moving from toxic and non-renewables to non-toxic and renewable materials (Graedel & Howard-Grenville 2005;Abdul Rashid et al 2008;Seliger et al 2008;Despeisse et al 2012). Outside of IE, research in the emerging niche of Sustainable Facilities Management can help in further studying how WM organizations might assist with facility aspects such as energy and emissions performance measures and green building design and evaluation (Nielsen et al 2016).…”
Section: Holistic Facility Managementmentioning
confidence: 99%